1982
DOI: 10.1080/00288233.1982.10417903
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the relationship between Argentine stem weevilListronotus bonariensis(Kuschel)) and several of its host grasses

Abstract: The susceptibilities of several New Zealand pasture grasses to Argentine stem weevil oviposition and larval attack were investigated. Short rotation cultivars of ryegrass showed higher susceptibility to both forms of attack than perennial ryegrass cultivars. It is possible that the latter ar.e resistant to weevil attack because of their comparatively high cellulose levels and consequent toughness. Of the other grasses, tall fescue was found to be highly resistant to egg-laying whereas Timothy was found to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 18 publications
5
39
0
Order By: Relevance
“…Infection of the host grass with fungal endophytes adds another dimension to this relationship, with the endophyte interacting with the plant genotype to influence the levels of alkaloids which are produced. The greater susceptibility of the tetraploid ryegrasses to ASW attack compared with the perennial ryegrasses is apparent in these trials and has been demonstrated before (e.g., Goldson 1982). Endophyte infection reduced the level of ASW attack considerably but the amount of damage inflicted on E+ Greenstone and Moata in our trials was in some instances similar to that on E-Nui and Pacific.…”
Section: Discussionmentioning
confidence: 68%
“…Infection of the host grass with fungal endophytes adds another dimension to this relationship, with the endophyte interacting with the plant genotype to influence the levels of alkaloids which are produced. The greater susceptibility of the tetraploid ryegrasses to ASW attack compared with the perennial ryegrasses is apparent in these trials and has been demonstrated before (e.g., Goldson 1982). Endophyte infection reduced the level of ASW attack considerably but the amount of damage inflicted on E+ Greenstone and Moata in our trials was in some instances similar to that on E-Nui and Pacific.…”
Section: Discussionmentioning
confidence: 68%
“…comm. ) and reports from Canterbury (Pottinger 1961;Goldson 1982). Identification of the factor Downloaded by [York University Libraries] at 03:43 18 November 2014 responsible for density dependent population regulation would increase our understanding of Argentine stem weevil population fluctuations and may lead to a new approach to control if the causal agent can be manipulated by farm management practices.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Prestidge et al (1982) cited weevil densities of c. 220 nr 2 in their nil endophyte ryegrass pastures. It can be conjectured that in all plots in this study there were sufficient volunteer non-endophyte ryegrass plants and other host grass species (e.g., Goldson 1982) to support the low numbers of weevils present, irrespective of the sown L. perenne. It is notable that significant inverse endophyte/peramine effects on adult weevil densities have been recorded in the same plots when the populations ranged downwards from 80 m~2 (L. R. Fletcher unpubl.…”
Section: Resultsmentioning
confidence: 99%